Dia de los muertos : a musical celebration [videorecording (DVD)] - Furloni, Mario; Jarrell, Todd; Yockey, James Burton; Hale, Randy (PBS, 2022)
Latino rock greats Los Lobos, the salsa-rap-reggae-funk Ozomatli and the all-female mariachi band Flor de Toloache lead this musical celebration of this much anticipated and highly celebrated fiesta by people of Mexican heritage everywhere. Taped before a live audience in the "underworld" of The Caverns subterranean amphitheater, ¡Día de los Muertos! is a high-energy offering to celebrate a wonderful, ancient tradition. Plus, in between performances, short vignettes explore the deep-rooted traditions and the meaning, origins, and importance of this holiday on the Latino calendar.